An illustrated key to and diagnoses of the species of Staphylinidae (Coleoptera) associated with decaying carcasses in Argentina - Aballay, Fernando Hernán (2014)
A key to 24 Staphylinidae species associated with decaying carcasses in Argentina is presented, including diagnoses, illustrations, distributional and bionomical data for these species. This article provides a table of all species associated with carcasses, detailing the substrate from which they were collected and geographical distribution by province. All 24 Staphylinidae species recorded are grouped into three subfamilies: Aleocharinae (three species of Aleochara Gravenhorst and one species of Atheta Thomson), Oxytelinae (one species of Anotylus Thomson) and Staphylininae (18 species, two belonging to the tribe Xantholinini and 16 species belonging to the tribe Staphylinini). A discussion is presented on the potential forensic importance of some species collected on human and pig carcasses.